Synthetic Study towards Strictamine: The Oxidative Coupling Approach - Ren, Weiwu; Tappin, Nicholas; Wang, Qian; Zhu, Jieping (Synlett, 2013)
A synthetic approach featuring a key intramolecular oxidative coupling of a dianion for the formation of the C7–C16 bond was exploited aiming at the synthesis of strictamine. Treatment of substituted tetrahydrocarboline with LHMDS at –78 °C followed by iodine at room temperature afforded a tetracyclic compound, a substructure of eburnane-type alkaloid, via the formation of the Na–C16 bond.
Keywords: strictamine; oxidative coupling; indole alkaloid; tetrahydro-β-carboline